Citations In Economics: Measurement, Uses, and Impacts - Hamermesh, Daniel S. (Journal of Economic Literature, 2018)
I describe and compare sources of data on citations in economics and the statistics derived from them. Constructing data sets of the post-publication citation histories of articles published in the “top five” journals in the 1970s and 2000s, I examine distributions and life cycles of citations, compare citation histories of articles in different subspecialties in economics, and present evidence on the history and heterogeneity of those journals' impacts and the marginal citation productivity of additional coauthors. I use a new data set of the lifetime citation histories of over 1,000 economists from thirty universities to rank economics departments by various measures and demonstrate the importance of intra- and interdepartmental heterogeneity in productivity. Throughout, the discussion summarizes earlier work, including the impacts of citations on salaries and nonmonetary rewards, and how citations reflect judgments about research quality in economics and the importance of economic ideas. (JEL A14, I23)